Exploring the Quality Gap of Thai Spa Services in UK - Kusol, Chompunuch (2008)
Given the increasing interest in Thai spa and massage among British and European people, this research assessed expectations and perceptions of service quality of Thai spa and massage operators and spa-goers in the UK by applying SERVQUAL model. SERVQUAL is an empirically derived method that can be used by service organisations such as spa operators to improve service quality. The process is to gain an understanding of the perceived service needs then compare against what organisation is excellent in service. The results of the gap analysis will then be used as a driver for service quality improvement. After a careful analysis of SERVQUAL, it has been found that the gap model of service quality is a powerful tool for Thai spa operators in the UK. In order to enhance the level of service quality, they require understanding the customer expectations and the key determinants of service quality which mean to spa-goers. The findings indicated, as a whole that the Thai spa operators in the UK do not understand customer expectations well, and the gaps between customer's expectations and perceptions are significant. In addition, there are also discrepancies in five key dimensions of service quality (reliability, responsiveness, assurance, empathy and tangibility) between managements' points of view and customers' standpoints.